We are all a little bit Cerberus: towards bioethical applicability of animalism - S. Yu. Shevchenko (Омский научный вестник: Серия "Общество. История. Современность")
I consider the applicability of the animalism in the framework of bioethical discussions — in particular related to situations in which a person is the cause of an event that is outside of her intentions, for example, infection with a dangerous disease. Animal or living organism are more adequate concept for posing this problem than the ‘Lockean’, psychological, personality. However, the conceptualization of the animal, proposed by the most famous animalist Eric Olson, turns out to be inappropriate for the bioethical formulation of bioethical problems. I suppose that Olson’s logic striving to cleanse the animal of everything that can be recognized as not proper part of it to some extent repeats the logic of constructing a transcendental subject. At the same time, the complexity of some bioethical problems emerges due to the impossibility of relying on the concept of a transcendental subject. The figure of Cerberus, a two-headed animal, and a single agent, allows to develop an alternative interpretation of the animal (living organism), more comprehensively characterizing who is involved in bioethical collisions. The article outlines the image of a single but distributed agent. As an example of such biological (animalistic), but also cognitive (psychological) distribution, I suggest the animal’s possession of the inner and skin microbiome.